2019
DOI: 10.1038/s41375-019-0382-3
|View full text |Cite
|
Sign up to set email alerts
|

CEBPA-mutated leukemia is sensitive to genetic and pharmacological targeting of the MLL1 complex

Abstract: The gene encoding the transcription factor C/EBPα is mutated in 10-15% of acute myeloid leukemia (AML) patients. N-terminal CEBPA mutations cause ablation of full-length C/EBPα without affecting the expression of a shorter oncogenic isoform, termed p30. The mechanistic basis of p30-induced leukemogenesis is incompletely understood. Here, we demonstrate that the MLL1 histone-methyltransferase complex represents a critical actionable vulnerability in CEBPA -mutated A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 57 publications
4
23
0
Order By: Relevance
“…The C/EBPα p30 variant can also exert specific functions through its interaction with epigenetic regulators. Affinity purification followed by mass spectrometry and co‐immunoprecipitation studies found that the p30 isoform preferentially interacted with the MLL1 methyltransferase complex, which catalyzes H3K4 tri‐methylation . Consistently, there was a large overlap in global chromatin association of C/EBPα p30 and the MLL1 complex.…”
Section: C/ebpα P30‐a Gain‐of‐function Variant?mentioning
confidence: 80%
See 3 more Smart Citations
“…The C/EBPα p30 variant can also exert specific functions through its interaction with epigenetic regulators. Affinity purification followed by mass spectrometry and co‐immunoprecipitation studies found that the p30 isoform preferentially interacted with the MLL1 methyltransferase complex, which catalyzes H3K4 tri‐methylation . Consistently, there was a large overlap in global chromatin association of C/EBPα p30 and the MLL1 complex.…”
Section: C/ebpα P30‐a Gain‐of‐function Variant?mentioning
confidence: 80%
“…Affinity purification followed by mass spectrometry and co-immunoprecipitation studies found that the p30 isoform preferentially interacted with the MLL1 methyltransferase complex, which catalyzes H3K4 trimethylation. [ 46 , 47 ] Consistently, there was a large overlap in global chromatin association of C/EBP α p30 and the MLL1 complex. These data indicate a cooperation of p30 with the MLL1 methyltransferase complex in the regulation of genes that are critical for the oncogenic effect of p30.…”
Section: C/ebp α P30-a Gain-of-function Variant?mentioning
confidence: 82%
See 2 more Smart Citations
“…In addition to MENIN/LEDGF or DOT1L, targeted interference with other components of the KMT2A fusion complexes (e.g., WDR5, BRD4, CDK9) have been explored in various preclinical models (125). Interestingly, AML cells carrying CEBPA mutations leading to expression of the short oncogenic CEBP/α p30 isoform appear sensitive to pharmacological targeting of the KMT2A complex (126). However, so far, no strategy has been reported that allows selective degradation of KMT2A fusion proteins to replicate the success in APL.…”
Section: Molecular Targeting Of Pediatric Amlmentioning
confidence: 99%